Age-Related Electrocardiographic Characteristics of Male Junior Soccer Athletes - Cavarretta, Elena; Sciarra, Luigi; Biondi-Zoccai, Giuseppe; Maffessanti, Francesco; Nigro, Antonia; Sperandii, Fabio; Guerra, Emanuele; Quaranta, Federico; Fossati, Chiara; Peruzzi, Mariangela; Pingitore, Annachiara; Stasinopoulos, Dimitrios M.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Very limited data exist on normal age-related ECGs variations in adolescents and no data have been published regarding the ECG anomalies induced by intensive training, which are relevant in pre-participation screening for sudden cardiac death prevention in the adolescent athletic population. The purpose of this study was to establish normal age-related electrocardiographic measurements (P wave duration, PR interval, QRS duration, QT and QTc interval) grouped according to 2-year age intervals. Methods: 2151 consecutive healthy adolescent Soccer athletes (trained for a mean of 7.2±1.1 hours per week 100% male Caucasians, mean age 12.4±1.4 years, range 7-18) underwent pre-participation screening, which included ECG and transthoracic echocardiography in a single referral center. Results: Heart rate progressively slowed as age increased (p<0.001, ranging from 80.8±13.2 to 59.5±10.2 bpm), as expected. P wave, PR interval and QRS duration significantly increased in older age classes (p=0.019, p=0.001 and p<0.001 respectively) and after Bonferroni's correction the difference remained significant in all age classes for QRS duration. QTc interval diminished progressively with increasing age (p=0.003) while QT interval increased progressively (p<0.001, Table 1). Conclusions: Significant variations in normal ECG characteristics of young athletes exist between different age groups related to increasing age and training burden, thus, age-specific reference values could be adopted, as already done for echocardiographic measurements, and may help to further discriminate potentially pathologic conditions.